2022
DOI: 10.31234/osf.io/fjtha
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How do people predict a random walk? Lessons for models of human cognition

Abstract: Repeated forecasts of changing targets are a key aspect of many everyday tasks, from predicting the weather to financial markets. Random walks provide a particularly simple and informative case study, as new values represent random deviations from the preceding value only, with further previous points being irrelevant. Moreover, random walks often hold simple rational solutions in which predictions should repeat the most recent state, and hence replicate the properties of the target. In previous experiments, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…The multiple chains of MC 3 introduce human-like long-range autocorrelations (see Figure 3D 3 ), and surprisingly, in both fixed target and random walk target tasks, this local sampling algorithm also produces almost no autocorrelations in the changes between estimates, but does show autocorrelations in the magnitude of these changes (see Figure 3E 3 ; Zhu, Sundh, et al, 2021). MC 3 better fit the overwhelming majority of participants in a price prediction task than non-sampling models of human behavior (Spicer, Zhu, et al, 2022a). Castillo et al (2022) showed that 'volitional' random generation could be explained as resulting from a related MCMC algorithm.…”
Section: Sampling Algorithms With Human-like Noisementioning
confidence: 93%
See 2 more Smart Citations
“…The multiple chains of MC 3 introduce human-like long-range autocorrelations (see Figure 3D 3 ), and surprisingly, in both fixed target and random walk target tasks, this local sampling algorithm also produces almost no autocorrelations in the changes between estimates, but does show autocorrelations in the magnitude of these changes (see Figure 3E 3 ; Zhu, Sundh, et al, 2021). MC 3 better fit the overwhelming majority of participants in a price prediction task than non-sampling models of human behavior (Spicer, Zhu, et al, 2022a). Castillo et al (2022) showed that 'volitional' random generation could be explained as resulting from a related MCMC algorithm.…”
Section: Sampling Algorithms With Human-like Noisementioning
confidence: 93%
“…But these sources could potentially be minor contributors, as argued by Drugowitsch et al (2016). Relatedly, Spicer, Zhu, et al (2022a) showed that almost all of their participants did not seem to exhibit any response noise (i.e., sampling algorithms without response noise fit the data better than sampling algorithms with response noise) after 0.37% of responses were excluded as outliers. However, sensory noise is still useful for explaining Weber's Law scaling of noise with stimulus magnitudes, as it is not obvious why that would arise from the sampling from hypotheses, and refining models of computational noise will in the future allow for more accurate partitioning of the different sources of noise.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…The same four versions of the models in experiment 1 were fitted to the serial prediction data in experiment 2. There were other models such as the MCMC model (Spicer et al, 2022) that may explain human's prediction of random walk better stepwise, but our interest was in the serial effects rather than the accuracy of prediction, and thus we did not implement and extend such models. We encourage future work to explore serial extensions of the random walk prediction models.…”
Section: Model Fittingmentioning
confidence: 99%
“…That said, if humans used the optimal strategy for making predictions, the outcomes of serial reproductions and serial predictions of random walk series would have been similar. In fact, there was good evidence that humans' predictions of random walk series deviate from this optimal strategy (Spicer, Zhu, Chater, & Sanborn, 2022;Zhu, Spicer, Sanborn, & Chater, 2021), but none of them so far focused on the serial effects of random walk predictions.…”
Section: Introductionmentioning
confidence: 99%